Sabun Lerak Peluang Kewirausahaan Untuk Meningkatkan Pertumbuhan Ekonomi Masyarakat - Nur Fitriana; Kornella kitty sitanggang; Azitiya; Aprilia Elsa Nadilla (CV. ITTC INDONESIA, 2025)
Entrepreneurship plays a crucial role in boosting economic growth by fostering innovation, creating job opportunities, and improving societal welfare. This study aims to analyze the role of entrepreneurship in economic development and the factors influencing its effectiveness. The research method used is a literature review of studies conducted over the past four years (2020-2024). The findings indicate that entrepreneurship significantly contributes to reducing unemployment, increasing national income, and strengthening business ecosystems through innovation and creativity. Additionally, the effectiveness of entrepreneurship can be analyzed using the SWOT approach, encompassing strengths, weaknesses, opportunities, and threats. Therefore, appropriate economic policies are necessary to create a conducive business environment for sustainable economic growth.